2010
DOI: 10.3233/jvr-2010-0522
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation readiness: A construct validity study of the University of Rhode Island Change Assessment for Vocational Counseling (URICA-VC) scale for persons with mental illness

Abstract: Purpose/objectives: The study aims to confirm the factorial structure of the URICA-Vocational Counseling (URICA-VC), a scale that has been specifically designed for use in vocational rehabilitation programs. Furthermore, the study explores the clinical utility of the URICA-VC readiness construct within a sample of individuals with psychiatric disabilities seeking competitive employment. Research method/design: Using a sample of 296 individuals with psychiatric disabilities pooled from three separate programs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Although the CWMEE-Employed theorized a five-factor model (including two factors within the preparation phase), our results identified a four-factor model. This outcome is consistent with previous research that identified three to four factors with varied stages of change scales developed for people with a range of disabilities who were unemployed [ 19 , 20 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although the CWMEE-Employed theorized a five-factor model (including two factors within the preparation phase), our results identified a four-factor model. This outcome is consistent with previous research that identified three to four factors with varied stages of change scales developed for people with a range of disabilities who were unemployed [ 19 , 20 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…The SOC model (Prochaska & DiClemente, 1983; Prochaska, DiClemente, & Norcorss, 1992) provides a comprehensive framework for intentional behavioral change of individuals with disabilities (Chou, Chan, & Tsang, 2004; Chou, Ditchman, Pruett, Chan, & Hunter, 2009; Strauser, 2013). This model has been widely used in vocational rehabilitation research to differentiate various cognitive and behavioral processes that occur in the intentional change process for target behavior including employment (Bezyak, Berven, & Chan, 2011; Chan, Miller, Lee, Pruett, & Chou, 2004; Da Silva Cardoso, Chan, Berven, & Thomas, 2003; Gervey, 2010; Strauser, 2013). The SOC model has five distinct stages, including (a) precontemplation (unawareness or denial of the problem), (b) contemplation (awareness of the problem and of the desired behavior change), (c) preparation (intention to take action), (d) action (practicing the desired behavior), and (e) maintenance (working to sustain the behavior).…”
Section: Introductionmentioning
confidence: 99%
“…The URICA's validity has been demonstrated in numerous studies (e.g., DiClemente & Hughes, 1990; Dozois, Westra, Collins, Fung, & Garry, 2004; McConnaughy, DiClemente, Prochaska, & Velicer, 1989; Polaschek, Anstiss, & Wilson, 2010). Further, URICA versions with special items for vocational counseling (Gervey, 2010) and domestic violence (Levesque, Gelles, & Velicer, 2000) are available, as well as a Chinese version (Chan, Chan, Siu, & Poon, 2007). A German version has been validated for patients with drinking problems (Fecht, Heidenreich, Hoyer, Lauterbach, & Schneider, 1998; Heidenreich, Hoyer, & Fecht, 2003; Hoyer, Heidenreich, Fecht, Lauterbach, & Schneider, 2003).…”
mentioning
confidence: 99%